TRANSFORMATIVE LIFE WRITINGTM: A FRAMEWORK FOR EMBEDDING STUDENT SOFT SKILLS? REFLECTIONS ON THE HIGHS AND LOWS OF DELIVERING A TRANSFORMATIVE CURRICULUM - Akhtar, Farrukh Nahid (PEOPLE: International Journal of Social Sciences, 2018)
The objectives of this reflective paper are two-fold. Firstly it considers the increasing marketization of UK HE and the subsequent need to embed student soft skills explicitly within curricula. Secondly, it introduces Transformative Life WritingTM (TLW) (a framework of transformative learning) and considers its usefulness as a medium of developing student soft skills. The author uses an auto-ethnographic approach to reflect on her experiences, of delivering a transformative curriculum by using TLW – a system that can facilitate profound personal and professional development through specific life writing tools. The rewards and challenges of using this approach are discussed, including the educator’s use of self and other strategies to create a safe environment in which students maximise their engagement, own and explore their emotional intelligence.It is argued that Transformative Life Writing can be an effective tool in increasing student awareness of their soft skills, and in increasing their confidence and self-esteem. This is especially so for vulnerable students, or those who consider themselves as having difficulties in engaging inter-personally with others. However, the paper highlights the needs of HEI’s to appropriately support educators in its delivery, especially in relation to the emotional labour involved.